Climate change and soil erosion in a small alpine lake basin on the Loess Plateau, China. Issue 8 (22nd November 2016) - Yu, Keke; Xu, Hai; Lan, Jianghu; Sheng, Enguo; Liu, Bin; Wu, Huixian; Tan, Liangcheng; Yeager, Kevin M.
Abstract: Multi‐proxy indices retrieved from sediments in Lake Chaonaqiu, an alpine lake on the western Loess Plateau (LP) of China, were used to reconstruct a precipitation history over the last 300 years. The results correlate well with records from tree rings and historical documents in neighboring regions. We show that the lake oscillated between two states, i.e. wetter climatic conditions, which favored denser vegetation cover, and promoted weaker catchment soil erosion; and drier climatic conditions, which lead to less vegetation coverage, correlate with stronger surface soil erosion. Several intensive soil erosion events were identified in the sediment cores, and most of these occurred during decadal/multi‐decadal dry periods, and correlate well with flood events documented in historical literature. The results of this study show that soil erosion by flood events is particularly intense during dry periods, and further highlights the role of vegetation cover in the conservation of water and soil in small lake basins on the Chinese LP. Copyright © 2016 John Wiley & Sons, Ltd.